New horizons in design science: Broadening the research agenda : 10th International Conference, DESRIST 2015, Dublin, Ireland, May 20-22, 2015, Proceedings - Donnellan, Brian; Helfert, Markus; Kenneally, Jim; VanderMeer, Debra; Rothenberger, Marcus; Winter, Robert (Lecture Notes in Computer Science, 2015)
This book constitutes the thoroughly refereed proceedings of the 10th International Conference on Design Science Research in Information Systems and Technology, DESRIST 2015, held in Dublin, Ireland, in May 2015. The 22 full papers, 11 short papers and 10 short papers describing prototypes and products were carefully reviewed and selected from 111 submissions. The papers are organized in topical sections on design science research in action; meta perspectives; data mining and analytics; emerging themes; design practice and design thinking; and prototypes.